2013
DOI: 10.3389/fncir.2013.00175
|View full text |Cite
|
Sign up to set email alerts
|

High concentrations of divalent cations isolate monosynaptic inputs from local circuits in the auditory midbrain

Abstract: Hierarchical processing of sensory information occurs at multiple levels between the peripheral and central pathway. Different extents of convergence and divergence in top down and bottom up projections makes it difficult to separate the various components activated by a sensory input. In particular, hierarchical processing at sub-cortical levels is little understood. Here we have developed a method to isolate extrinsic inputs to the inferior colliculus (IC), a nucleus in the midbrain region of the auditory sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 52 publications
1
23
0
Order By: Relevance
“…Thus, there is a complex convergence of local and ascending inputs on neurons in the IC that creates a complex internal microcircuitry. Recent physiological studies have emphasized the importance of the local connections within the IC for the neural processing of sound (Chandrasekaran et al, 2013; Grimsley et al, 2013; Sivaramakrishnan et al, 2013). Nevertheless, little is known about how specific neuron types in the IC contribute to the local microcircuitry.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there is a complex convergence of local and ascending inputs on neurons in the IC that creates a complex internal microcircuitry. Recent physiological studies have emphasized the importance of the local connections within the IC for the neural processing of sound (Chandrasekaran et al, 2013; Grimsley et al, 2013; Sivaramakrishnan et al, 2013). Nevertheless, little is known about how specific neuron types in the IC contribute to the local microcircuitry.…”
Section: Introductionmentioning
confidence: 99%
“…The convergence that results from the recruitment of auditory afferent inputs with sound pressure level (Sachs and Abbas, 1974) is inadequate to cover the ~110 dB range of normal hearing (Spirou et al, 1999; Young and Sachs, 2008), implying that ascending input alone is insufficient to generate a monotonically increasing firing rate over the whole intensity range. In the midbrain nucleus of the inferior colliculus (IC), afferent lemniscal activation in brain slices recruits local circuits that prolong synaptic responses (Sivaramakrishnan et al, 2013). At high levels of afferent recruitment, synaptic potentials have prolonged plateau depolarizations that increase the duration and rate of firing (Sivaramakrishnan et al, 2004; Sivaramakrishnan and Oliver, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The central nucleus of the IC receives massive input convergence from lower auditory nuclei and corticofugal projections, and local circuits connect layers of cells that receive inputs at different frequencies (Oliver et al, 1991, 1997; Chase and Young, 2005; Chandrasekaran et al, 2013). To test the role of local circuits in forming codes of sound intensity, we applied a high concentration of divalent cations (HiDi; raised Ca 2 + and Mg 2 + concentrations; Frankenhaeuser and Hodgkin, 1957) locally in the IC during changes in sound intensity, to isolate monosynaptic from local inputs (Sivaramakrishnan et al, 2013). We found that as sound intensity increased, the source of recruited synapses changed from monosynaptic to local.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to brain stem inputs, local midbrain projections may target and interact with neurons differentially across an ICC lamina that could result in subregions with different functional properties. A recent study that differentiated between monosynaptic inputs from local polysynaptic inputs within the inferior colliculus found that monosynaptic inputs have short latencies, whereas local polysynaptic inputs result in variable onset times and evoke long-lasting excitation (Sivaramakrishnan et al 2013). Together with our results showing that caudal-and-medial regions respond with longer, more diverse latencies and longer PSTH durations than rostral-and-lateral regions, this suggests that local polysynaptic midbrain circuits may be targeting and activating the caudal-and-medial regions to a larger extent.…”
Section: Mechanisms Underlying Response Mapsmentioning
confidence: 99%